KUALITAS PELAYANAN PERIZINAN NON USAHA MELALUI SISTEM PELAYANAN ELEKTRONIK ( SIMPEL ) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KARANGANYAR - Prasetiawan, Nanda; Suhita, Damayanti; Wirawan, Riska (Solidaritas, 2024)
Karanganyar Regency carries out integrated service policy responsibilities organized by the One Stop Integrated Service and Investment Service (DPMPTSP). This service is a digital-based non-business licensing service called SIMPEL (Electronic Service System). Practically, people manage their service needs all through an electronic service system. Through the SIMPEL service system, all non-business licensing arrangements can be carried out more easily, quickly, precisely and efficiently.The type of research used is descriptive qualitative. This research aims to describe the quality of non-business licensing services through a simple application at the Karanganyar Regency Investment and One-Stop Integrated Services Service using the theory of Zeithaml, Parasuraman, Berry (in Hardiansyah (2011:41)). This model states that the success of service quality is determined by 5 indicators which serve as benchmarks for measuring service quality, these indicators are physical evidence, reliability, responsiveness, assurance, empathy In the results of research on real variables (physical evidence) based on the information used in obtaining permits which is quite easy, researchers also found that the ease of access to information available on the SIMPEL website is said to be good. In the Reliability variable, employees have followed the SOP as a work guide, and understand what information will be conveyed by the public as service users. In the Responsiveness variable, employees serve service users quickly and respond to every online and online service user. offline. In the Assurance variable, it can be said that the cost indicators and security guarantees are good and the employees are polite, courteous and friendly. The Emphaty indicator in prioritizing the interests of service users is said to be quite good, as can be seen from the statements of informants interviewed by researchers in the field. Informants expressed satisfaction with the service on this indicator. It can be concluded that all indicators carried out by researchers have worked well. Apart from that, it is recommended to DPMPTSP Karanganyar to further maximize employee performance and improve services that are already running well in accordance with the SOP and objectives of DPMPTSP Karanganyar Regency.  Keywords: Service quality, Licensing, SIMPEL Implementation